2020
DOI: 10.2147/amep.s246901
|View full text |Cite
|
Sign up to set email alerts
|

<p>Challenges Faced by Nursing Students to Work with Nursing Personnel: A Qualitative Study</p>

Abstract: Purpose: Nursing is a practice-based discipline. Clinical education is one of the most important parts of nursing education; nurses play an important role in the learning of nursing students. This study was carried out to unveil the challenges of nursing students' learning through working with nurses. Methods: A qualitative design was used to conduct the study in city of Khalkhal, Ardabil province, Iran. In order to collect data through purposive sampling, twenty students were interviewed using in-depth semi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Makarem et al ( 2019 ), for example, found that nurses do not have much professional confidence during their first 10 years of work, while Kalyani et al ( 2019 ) state that nurses are not competent at teaching nursing students. In the same vein, Moghaddam et al ( 2020 ) reported that nurses' lack of teaching skills is a barrier to student learning. In terms of language being a barrier to student learning, similar findings were reported in a study by Ashipala and Matundu ( 2023 ), who found that a poor command of the language of the clinical environment can result in unfavorable or unpleasant experiences and poor learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Makarem et al ( 2019 ), for example, found that nurses do not have much professional confidence during their first 10 years of work, while Kalyani et al ( 2019 ) state that nurses are not competent at teaching nursing students. In the same vein, Moghaddam et al ( 2020 ) reported that nurses' lack of teaching skills is a barrier to student learning. In terms of language being a barrier to student learning, similar findings were reported in a study by Ashipala and Matundu ( 2023 ), who found that a poor command of the language of the clinical environment can result in unfavorable or unpleasant experiences and poor learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additional challenges to CLE include mistreatment by patients, difficulties in managing patients from unfamiliar cultural backgrounds ( Drateru, 2019 ), negative perceptions of the nursing profession, insufficient commitment of nurses to patient care, disrespect, student abuse, and a lack of appreciation ( Moghaddam et al, 2020 ). Furthermore, students may face unpreparedness for clinical training when they grapple with anxiety stemming from concerns about making mistakes, uncertainty regarding patients, and confusion about the practical aspects of nursing ( Günay & Kılınç, 2018 ; Joolaee et al, 2015 ), along with a fear of peer assessment and apprehension about receiving negative feedback from clinical instructors ( Bazrafkan & Kalyani, 2018 ; Kalyani et al, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additional challenges that warrant exploration are more closely tied to students’ experiences in clinical settings. They often complain to their clinical instructors that some clinical settings are not conducive to learning, mainly because some preceptors are uncooperative and unsupportive ( Aboshaiqah et al, 2018 ; Moghaddam et al, 2020 ; Thomas et al, 2018 ) and many patients reject them because they prefer to receive care from qualified nurses ( Joolaee et al, 2015 ; Drateru, 2019 ). These issues may impact students’ self-esteem and motivation for clinical skill acquisition ( Buthelezi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations